Mito-Tempo improves acrosome integrity of frozen-thawed epididymal spermatozoa in tomcats - Hiba Ali Hassan; Penelope Banchi; Penelope Banchi; Guillaume Domain; Leen Vanderheyden; Sylwia Prochowska; Wojciech Nizański; Ann Van Soom (Frontiers in Veterinary Science, 2023)
IntroductionIn tomcats, epididymal spermatozoa provide an additional source of male gametes available for cryopreservation. While this procedure is feasible, the survival rate and motility of epididymal cat spermatozoa are both low after thawing. Cryopreservation is known to induce oxidative stress in spermatozoa, with mitochondria and the plasma membrane being the two major generation sites, and an imbalanced presence of free radicals is a possible cause for this low survival rate. Different antioxidants have been tested before for their effect on cryopreserved cat spermatozoa quality, with varying results. Here, we used Mito-Tempo, which is a synthetic mitochondria-targeted antioxidant and a specific scavenger of the mitochondrial superoxide system. By supplementing Mito-Tempo with the freezing extender, we aimed to improve the sperm quality of frozen-thawed cat epididymal spermatozoa.MethodsEpididymal spermatozoa obtained from twelve tomcats were assessed for motility and concentration. Prior to freezing, samples were diluted in TRIS buffered extender with egg yolk and glycerol and divided into five aliquots supplemented with 0 (control), 0.5, 5, 50, and 1005M of Mito-Tempo. After thawing, sperm motility, concentration, morphology, plasma membrane integrity, acrosome integrity, and mitochondrial membrane potential were evaluated. A Friedman rank sum test with a Bonferroni post-hoc test was used to determine statistical in-between group differences in post-thaw semen parameters.Results and discussionThe results indicated a slight improvement in acrosome integrity across all groups that were supplemented with Mito-Tempo, with the group that received 55M of Mito-Tempo showing the greatest improvement [(median of 67.99%, IQR of 5.55) compared to the control group (median of 65.33%, IQR of 7.75; P = 0.05)]. For all other sperm parameters, no significant differences (P > 0.05) were detected between different Mito-Tempo concentrations. These findings highlight the protective effect of Mito-Tempo on acrosome integrity and suggest that 55M is the most effective concentration for maintaining acrosome integrity. Since Mito-Tempo has shown a positive effect on multiple sperm parameters in other species, such as men, boars, roosters, rams, and bulls, we need to conclude that species-specificity may play a role here.